Building Capacity for Decentralization and Local Governance in Sub-Saharan Africa : The Municipal Development Program - Sevilla, M. (World Bank, Washington, DC, 2012)
The Municipal Development Program (MDP) ws launched in 1991 with the World Bank as the executing agency and with the support of several donors to assist the governments in building local government capacity. The Program reflects the belief that since locally-elected officials are usually more in touch with the public than their central government counterparts, there is greater likelihood that the policies chosen will reflect the concerns of the committees and also be more accountable to them. The MDP is a facility that provides quick-disbursing grants to local executing authorities for policy development and capacity building. Support is made in the form of small grants and consultants, using action planning workshops and asissting in strategic planning aimed at providing management tools and adding key skills to selected staff. The MDP has been able to do this because of its design which allows for flexibility and easy access to funds, and its focus--local municipalities.